2012
DOI: 10.1371/journal.pone.0039293
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cytokinin Derivatives Do Not Show Negative Effects on Root Growth and Proliferation in Submicromolar Range

Abstract: BackgroundWhen applied to a nutrition solution or agar media, the non-substituted aromatic cytokinins caused thickening and shortening of the primary root, had an inhibitory effect on lateral root branching, and even showed some negative effects on development of the aerial part at as low as a 10 nanomolar concentration. Novel analogues of aromatic cytokinins ranking among topolins substituted on N9-atom of adenine by tetrahydropyranyl or 4-chlorobutyl group have been prepared and tested in standardized cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 55 publications
(75 reference statements)
3
33
0
Order By: Relevance
“…2). Similarly to our previous results, 14 the application of 50 nM 3MeOBA9THPP had positive effect on primary root elongation when compared with untreated controls (cp. primary root lengths: 11.4 ± 1.2 cm vs. 9.9 ± 0.6 cm).…”
supporting
confidence: 89%
See 4 more Smart Citations
“…2). Similarly to our previous results, 14 the application of 50 nM 3MeOBA9THPP had positive effect on primary root elongation when compared with untreated controls (cp. primary root lengths: 11.4 ± 1.2 cm vs. 9.9 ± 0.6 cm).…”
supporting
confidence: 89%
“…14 We found that the THP group can be cleaved off from its parent CK both in the root and the leaf. Subsequently, the free base can be glycosylated at the N9 position to provide the glucoside or riboside.…”
mentioning
confidence: 77%
See 3 more Smart Citations